Propuesta de gestión efectiva en cartera morosa – caso estudio: Previser, Servicios intangibles (2024)
The effective management process in the collection of overdue accounts aims to transform accounts receivable into liquid assets in the shortest time possible, reversing the negative impact on the company's cash flow or working capital.